WAYS OF FORMING LOGICAL CULTURE OF STUDENTS WHEN TEACHING MATHEMATICS - Bekbolganova А.Қ. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
The relevance of the article is determined by the fact that the most important direction of reforming the country’s education system is to focus on personal development in accordance with the characteristics, personal capabilities, aptitudes and abilities. Full-fledged human activity in modern society, its daily life and professional activities require a high level of General development, a common culture. The article considers the possibilities aimed at forming a culture of students ’ thinking and developing the student’s personality. In the process of teaching mathematics, the role of the student’s search activity is determined, which leads to mastering the methods and techniques that represent the creation of the educational process in accordance with the structure of the activity, the features of creative mathematical activity, and the formation of a General culture of students ’ thinking. Logical Culturology is a very broad and complex concept. Because these qualifications are necessary to people of any profession. In addition, the article presents the opinions of scientists who have studied this topic as clear evidence. Based on the opinions of scientists, we consider the possibilities of developing students ’ logical thinking in the educational process and various ways to solve problems